The moral dimension in the management of money and prophetic works - tashtoush, Hayel abd al mawla (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aims to clarify and explain the role of the Prophet in establishing and consolidating the rules and foundations of the science of management in general and business administration in particular, and the reason is the belief of many researchers throughout the world that the establishment of the State of the city and the management of the Prophet peace be upon him was random and Based on the basis of knowledge or scientific, so this study came to clarify the matter and revelation; and focuses on the moral aspect of business management, because of the importance of ethics and its necessity in dealing with people and events and this is the body of the Holy Prophet during the various stages of building and NH Medina. The importance of this study stems from the fact that it will shed light on the importance of ethics and its effective role in the success and progress of the science of management in general and the management of business in particular.